COMPARISON OF ALGORITHMS FOR DETERMINATION OF ROTATION MEASURE AND FARADAY STRUCTURE. I. 1100-1400 MHZ - Sun, X. H.; Rudnick, L.; Akahori, Takuya; Anderson, C. S.; Bell, M. R.; Bray, J. D.; Farnes, J. S.; Ideguchi, S.; Kumazaki, K.; O'Brien, T.; O'Sullivan, S. P.; Scaife, A. M. M.; et al. (The Astronomical journal, 2015)
ABSTRACT Faraday rotation measures (RMs) and more general Faraday structures are key parameters for studying cosmic magnetism and are also sensitive probes of faint ionized thermal gas. A definition of which derived quantities are required for various scientific studies is needed, as well as addressing the challenges in determining Faraday structures. A wide variety of algorithms has been proposed to reconstruct these structures. In preparation for the Polarization Sky Survey of the Universe's Magnetism (POSSUM) to be conducted with the Australian Square Kilometre Array Pathfinder and the ongoing Galactic Arecibo L-band Feeds Array Continuum Transit Survey (GALFACTS), we run a Faraday structure determination data challenge to benchmark the currently available algorithms, including Faraday synthesis (previously called RM synthesis in the literature), wavelet, compressive sampling, and QU-fitting. The input models include sources with one Faraday thin component, two Faraday thin components, and one Faraday thick component. The frequency set is similar to POSSUM/GALFACTS with a 300 MHz bandwidth from 1.1 to 1.4 GHz. We define three figures of merit motivated by the underlying science: (1) an average RM weighted by polarized intensity, , (2) the separation of two Faraday components, and (3) the reduced chi-squared . Based on the current test data with a signal-to-noise ratio of about 32, we find the following. (1) When only one Faraday thin component is present, most methods perform as expected, with occasional failures where two components are incorrectly found. (2) For two Faraday thin components, QU-fitting routines perform the best, with errors close to the theoretical ones for but with significantly higher errors for . All other methods, including standard Faraday synthesis, frequently identify only one component when is below or near the width of the Faraday point-spread function. (3) No methods as currently implemented work well for Faraday thick components due to the narrow bandwidth. (4) There exist combinations of two Faraday components that produce a large range of acceptable fits and hence large uncertainties in the derived single RMs; in these cases, different RMs lead to the same behavior, so no method can recover a unique input model. Further exploration of all these issues is required before upcoming surveys will be able to provide reliable results on Faraday structures.